Smit, Dirk J., Remembering theologians – Doing theology. Collected essays 5 - R. van Deventer (Acta Theologica)
From text: Over the years, Dirkie Smit established himself as one of South Africa’s pre?eminent theologians. The publication – by Sun Press – of his academic articles in the form of “Versamelde  Opstelle” and “Collected Essays” – already five books up to date – furnishes ample reason why he is highly respected by fellow theologians. Not only is he exceptionally productive with an overwhelming output, but he is also encyclopaedically informed about developments in theology. More important, his work breathes a constructive graciousness that is truly impressive.